Cost-Effectiveness of Thoracotomy Approach for the Implantation of a Centrifugal Left Ventricular Assist Device. Issue 8 (August 2020) - Mahr, Claudius; McGee, Edwin; Cheung, Anson; Mokadam, Nahush A.; Strueber, Martin; Slaughter, Mark S.; Danter, Matthew R.; Levy, Wayne C.; Cheng, Richard K.; Beckman, Jennifer A.; May, Damian M.; Ismyrloglou, Eleni; et al.
Abstract : This study reports the first analysis regarding cost-effectiveness of left ventricular assist device (LVAD) implantation via thoracotomy. Cost-effectiveness of LVADs implanted via the traditional surgical approach of sternotomy has been improved through the years because of technological advances, along with understanding the importance of patient selection and postimplant management have on positively affecting outcomes. Given the positive clinical outcomes of the thoracotomy approach, we seek to study the cost-effectiveness of a centrifugal LVAD via this less invasive approach. We developed a Markov model. Survival and quality of life inputs (QALY) for the LVAD arm were based on data from the LATERAL clinical trial. For the Medical Management arm, survival was derived from the Seattle Heart Failure Model. The heart transplant probability was derived from INTERMACS. Survival after heart transplantation used International Society for Heart and Lung Transplantation data. Cost inputs were calculated based on Medicare data and past literature. The incremental cost-effectiveness ratio was found to be $64, 632 per quality adjusted life year and $57, 891 per life year in the bridge to transplant indication. These results demonstrate further improvement in the overall cost-effectiveness of LVAD therapy and confirm implantation of LVADs via a less invasive approach as being cost-effective. Abstract : Supplemental Digital Content is available in the text.